Surface charge characteristics of a variable charge soil (Rhodic Ferralsols) in the Central Highlands - Quang Chon Nguyen; Van Cuong Dinh; Minh Ngoc Truong (Vietnam Journal of Science, Technology and Engineering, 2020)
Variable charge soils (VCS) predominantly contain minerals with variable surface charge density, such as kaolinite, gibbsite, goethite, hematite and amorphous minerals. The charge characteristics differ between profile horizons, the topsoil normally possesses net negative surface charge whereas the subsoil may have net positive surface charge and are largely dependent on soil pH. The soils pose a particular challenge to sustainable management in terms of low cation exchange capacity (CEC) at soil low pH and may develop appreciable anion exchange capacity (AEC) under acidic conditions. A full understanding of the variation of charge with soil pH, before establishing strategies for sustainable management of these soils, is essential. This study has found that the VCS from the Central Highlands are extremely acidic (pH<4.5) and very low in CEC (<1.0 cmolc kg-1), these problems are more pronounced in the subsoil with exhibiting higher pH0 (4.63) than the existing soil pH (4.26) and higher point of zero net charge (PZNC) (4.88) than point of zero charge (pH0), and developing net positive surface charge (-0.62 cmolc kg-1). These properties are attributed to low total organic carbon (TOC) and Fe/Al hydrous oxides in the clay fraction that significantly affect pH buffering capacity and delta CEC. In addition, organic matter (OM) has a great influence on the pH0 of variable charge components, and thus on CEC.